TSLP Production Induced by Poly(I:C) Stimulation Increased in the Presence of Th2 Cytokines in Patients with Severe ECRS - Inoue, Akiko; Tanaka, Yuriko; Matsui, Hidehito; Fukuo, Akira; Kondo, Motonari; Wada, Kota (International Archives of Otorhinolaryngology, 2025)
In patients with eosinophilic chronic rhinosinusitis (ECRS), viral infection of the upper respiratory tract tends to exacerbate the symptoms.To clarify the effect of the cytokines during viral infection in ECRS patients, we investigated the production of thymic stromal lymphopoietin (TSLP) in the sinus mucosa of ECRS patients in the presence of polyinosinic: polycytidylic acid, or poly(I:C), which mimics viral infection, with or without interleukin-4 (IL-4) or IL-13.The ECRS patients were classified into mild, moderate, and severe groups based on the scoring system of the Japanese Epidemiological Study of Refractory Eosinophilic Chronic Rhinosinusitis (JESREC). We obtained paranasal sinus mucosa from patients with ECRS through endoscopic sinus surgery, as well as nasal epithelial cells. The cells were stimulated with poly(I:C) in the presence or absence of IL-4 or IL-13. The TSLP concentrations in the culture supernatants were measured using enzyme-linked immunosorbent assay (ELISA) after 24 hours of stimulation.Nasal epithelial cells from patients with ECRS or healthy controls produced TSLP upon stimulation with poly(I:C) alone, and the addition of IL-4 or IL-13 increased TSLP production. Notably, the increase in poly(I:C)-induced TSLP production from nasal epithelial cells in the presence of IL-4 or IL-13 was greater among the severe group compared to the other groups.In the sinus mucosa of patients with severe ECRS, TSLP production was enhanced more when poly(I:C) stimulation was combined with IL-4 or IL-13 stimulation. Thus, the Th2-skewed condition of the sinus mucosa during viral infection in patients with more severe ECRS may accelerate disease exacerbation.
Keywords: thymic stromal lymphopoietin; Th2 cytokine; eosinophilic chronic rhinosinusitis